Analisis Konflik Sosial Santri Reguler dan Intensif di TMI Putra Al-Amien Prenduan - Munir, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article describes the conflict that occurred between Regular and Intensive santri at TMI Putra al-Amin Prenduan. The data collection method used is comparing observational data with the results of interviews with triangulation. Humans are born to know each other and socialize. But everyone also has to live in groups. Problems arise when there is a conflict of social relations between groups and a lack of social communication that occurs due to several things. The conflict that occurred among the Regular and Intensive santri at TMI Putra al-Amin Prenduan, which resulted in a lack of social communication and admonished the santri. This is due to provocative words that often arise among santri, causing emotion within themselves to be very high which results in the emergence of hostility among santri. From the data obtained, about the Regular and Intensive santri social groups there are three that cause conflicts to occur between santri, namely: the mischief of the santri, the behavior of the santri and the social interaction of the santri. While the causes of the Regular and Intensive santri conflict in TMI Putra Al-Amien Prenduan are caused by three things, namely: the factor of the older brother's doctrine, fanatics and bullying.